LGBTQ Tourism in Thailand in the Light of Glocalization Capitalism, Local Policies, and Impacts on the Thai LGBTQ Community - Veilleux, Alexandre (Nuove Geografie. Strumenti di lavoro, 2021)
For many decades, Thailand has been described as a "gay paradise" by various travel magazines and Bangkok is often referred to as the "gay capital of Asia". However, local LGBTQ people are still facing discrimination in many aspects of their life and many rights are denied to people of various sexual orientations and identities. In this era of globalisation, tourism brings stronger connections between countries, increasing exchanges of ideas and customs among different populations, such as ideas and values relating to sexual identities. Yet, very few studies have tried to link tourism with the processes of political and legal change, especially regarding LGBTQ rights. Moreover, it is still uncertain if LGBTQ tourism can have an impact beyond economic benefits in the destination. Therefore, the purpose of this research is to find out what are the impacts of LGBTQ tourism on the Thai LGBTQ community and on Thai legislation regarding people of various sexual orientations. Using qualitative data collected through semi-structured interviews, document analysis, and semiotic theory, the research shows how LGBTQ tourism in Thailand witnessed major transformations in the last 50 years, while emphasizing how the government and those in power have used this niche market for their own benefits. The findings show contradictory elements between the rhetoric that promotes Thailand as a "gay paradise" for tourists and the situation for local LGBTQ people. Yet, the study also shows how LGBTQ tourism can positively impact LGBTQ rights in the destination. At last, the study responds to criticism of pinkwashing by putting Thailand into its own cultural context.